Fas/Fas Ligand Interaction Contributes to UV-Induced Apoptosis in Human Keratinocytes - Martin Leverkus; Mina Yaar; Barbara A. Gilchrest (1997)
Keratinocytes in human skin undergo apoptosis during various inflammatory processes and after ultraviolet (UV) irradiation. To determine if keratinocyte apoptosis may be mediated by the Fas/APO-1 receptor (CD95), a signal transduction pathway known to initiate programmed cell death of lymphocytes, we investigated Fas expression, modulation, and function in keratinocytes. Keratinocytes constitutively expressed the 2.5- and 1.9-kb Fas transcripts, as well as the 43-kDa Fas protein. Treatment of interferon-γ-stimulated keratinocytes with Fas agonistic antibody significantly promoted their cell death, indicating that Fas in keratinocytes is functional. UV irradiation induced Fas mRNA expression within 16 to 24 h and Fas protein within 24 h and through 48 h after irradiation. Furthermore, keratinocytes constitutively expressed Fas ligand (FasL) mRNA and protein. UV irradiation induced FasL mRNA as early as 4 h after irradiation and elevated FasL mRNA levels were maintained for at least 24 h postirradiation. Moreover, a FasL neutralizing antibody significantly reduced UV-induced apoptosis of IFN-γ-treated keratinocytes. Our data strongly suggest that the Fas system contributes to keratinocyte apoptosis in UV-irradiated human skin.